Legal Analysis of Articles of Association Amendments That Cause Share Dilution: Implications for Minority Shareholders' Rights - Ferdinandus Zulvacar, Nathanael Ezekiel; Ariawan Gunadi (Universitas Semarang, 2025)
This study analyzes the juridical validity of amendments to articles of association that lead to share dilution and their implications for minority shareholders in Indonesian corporate law. The urgency arises from the growing number of corporate actions that, while procedurally legal, result in substantive disadvantages for minority shareholders, creating governance imbalances. Using a normative juridical method, the research examines relevant laws, doctrines, and legal principles governing shareholder protection in share dilution cases. The findings reveal that amendments to articles of association often result in a loss of ownership percentage and voting power for minority shareholders due to inadequate safeguards such as pre-emptive rights. The study highlights the gap between formal legal compliance and substantive fairness, identifying weaknesses in both enforcement and regulatory oversight. The novelty of this research lies in its focus on the intersection between corporate governance and minority rights in the context of articles of association amendments, an area that remains underexplored in Indonesian legal scholarship. The study concludes that current protections are insufficient and recommends legal reforms, including enhanced minority veto rights, stronger enforcement mechanisms, and the institutionalization of accessible dispute resolution avenues.